(untitled) (Circe de clásicos y modernos, 2018)
In this paper I present a state of the art of the implications that the comparison between the writings of Philo of Alexandria and those produced by the rabbis of the first centuries CE have for the study of ancient and late ancient Judaism in general and the rabbinic movement in particular. This not only leads to a problematization of the parallelisms between the Philonic texts and the rabbinical ones, but also the morphology of Judaism in both periods.